2017
DOI: 10.1186/s12917-017-1095-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety pharmacology and subchronic toxicity of jinqing granules in rats

Abstract: BackgroundJinqing granules which are made of a mixture extract that contains Radix Tinosporae and Canarii fructus in proportions according to a longstanding formula have a good effect on the prevention and treatment of gastric ulcer disease. It has not been through safety through systematic toxicological studies, however. To provide basis for clinical application, we performed safety pharmacology and subchronic toxicity experiments in specific pathogen-free Sprague-Dawley rats.ResultsIn safety pharmacology exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…At the end of experiment, rats were fasted for 10–12 h before blood sampling. Rats were euthanatized with 1% pentobarbital sodium (intraperitoneal injection, 30 mg/kg), and then the blood samples were withdrawn from the heart into different vacuum tubes [56]. The blood in Na-heparin vacuum tubes were used for hematological measurement which was performed in one hour.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of experiment, rats were fasted for 10–12 h before blood sampling. Rats were euthanatized with 1% pentobarbital sodium (intraperitoneal injection, 30 mg/kg), and then the blood samples were withdrawn from the heart into different vacuum tubes [56]. The blood in Na-heparin vacuum tubes were used for hematological measurement which was performed in one hour.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that both Pd and Pt NPs did not induce toxicity in aquatic organism, Daphnia magna [ 43 ]. In our study, the organ coefficient was determined for evaluating the toxicity of PdPt bimetallic NPs on target organs of mice [ 44 , 45 ]. As shown in Table 1 , no differences were found in the organ coefficient of heart, liver, spleen, lung, kidney and brain among different groups ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results we determine whether the model was successful. Organ coefficient is a common indicator of chronic toxicity [ 35 , 36 ]. We clarified that Asarum can lead to increased organ coefficients.…”
Section: Discussionmentioning
confidence: 99%